Implementation Of The Edupreneur Approach In The Development Of Ginzberg’s Theory For Optimizing Student Career Decision Making - Hasanah, Jeni Fadhilatul; Isriyah, Mudafiatun; Fauziyah, Nailul (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2025)
Career selection is a complex process that requires a deep understanding of interests, talents, personal values, and the realities of the job market. Among vocational high school (SMK) students, the challenges in career decision-making remain high, primarily due to low self-awareness and a lack of entrepreneurial orientation. This study aims to implement the edupreneurial approach in the development of Ginzberg's theory, particularly in the tentative stage, to optimize students' career decision-making abilities. The method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to design a career guidance module that integrates entrepreneurial values. After validity testing, the module was applied to 8 students in the eleventh grade at SMKS Muhammadiyah Jember. The results indicate that the integration of Ginzberg's theory and the edupreneurial approach enhances self-awareness, creativity, and students' readiness to determine their career paths. Quantitative analysis using the Paired Sample T-Test shows a significant improvement from an average pre-test score of 140.50 to a post-test score of 159.25 (p < 0.05). Although the correlation between the pre-test and post-test is low (0.189), the significant difference indicates a positive impact of the module. Qualitative analysis reveals that students showed a high interest in the module's content and felt more confident in making career decisions. Overall, this module is effective in enhancing students' career decision-making abilities and creating a positive learning environment. This study recommends that career guidance in vocational schools adapt curricula and counseling services that are more responsive to the dynamics of entrepreneurship.